Hematological Biomarkers for Differentiating Peritonsillar Abscess from Acute Tonsillitis: A Retrospective Analysis of MPV, SII and PCT - BABAR RAFIQ KHAN; HAFIZ SAJJAD HYDER; USAMA AHMAD; HUSNAIN AHMED (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Acute tonsillitis can cause peritonsillar abscess (PTA), which can be treated medically. Complete blood count (CBC) indicators are increasingly used to diagnose illness. Aim: To investigate if biomarkers can distinguish acute tonsillitis from PTA and uncover characteristics that can predict PTA. Methods: In a retrospective study, CBC-derived biomarkers like MPV, NLR, PLR, SII, IDI, PCT, and LMR were compared between septoplasty patients (n=67) and acute tonsillitis patients (n=107). This statistical analysis also included tonsillitis with PTA (n=52) and isolated tonsillitis (n = 55). Biomarkers’ prediction capacities were assessed using ROC analysis to determine their accuracy. Results: There were significant changes in MPV, SII, and PCT between tonsillitis and PTA subgroups (P = 0.010, 0.021, and 0.023). Differences were statistically significant. ROC analysis showed that the AUC for PTA prediction was 0.644 (MPV), 0.63 (SII), and 0.627 (PCT). MPV sensitivity and specificity were 51.9–72.7%, SII 94.2–32.7%, and PCT 71.2–50.9%. SII levels were greatest. Conclusions: MPV, SII, and PCT may aid clinicians in predicting PTA development in acute tonsillitis, guiding decisions for imaging or intervention. Keywords: Acute tonsillitis, biomarkers, mean platelet volume, peritonsillar abscess